WIP1 Promotes Homologous Recombination and Modulates Sensitivity to PARP Inhibitors - Burdova, Kamila; Storchova, Radka; Palek, Matous; Macurek, Libor (Cells, 2019)
Genotoxic stress triggers a combined action of DNA repair and cell cycle checkpoint pathways. Protein phosphatase 2C delta (referred to as WIP1) is involved in timely inactivation of DNA damage response by suppressing function of p53 and other targets at chromatin. Here we show that WIP1 promotes DNA repair through homologous recombination. Loss or inhibition of WIP1 delayed disappearance of the ionizing radiation-induced 53BP1 foci in S/G2 cells and promoted cell death. We identify breast cancer associated protein 1 (BRCA1) as interactor and substrate of WIP1 and demonstrate that WIP1 activity is needed for correct dynamics of BRCA1 recruitment to chromatin flanking the DNA lesion. In addition, WIP1 dephosphorylates 53BP1 at Threonine 543 that was previously implicated in mediating interaction with RIF1. Finally, we report that inhibition of WIP1 allowed accumulation of DNA damage in S/G2 cells and increased sensitivity of cancer cells to a poly-(ADP-ribose) polymerase inhibitor olaparib. We propose that inhibition of WIP1 may increase sensitivity of BRCA1-proficient cancer cells to olaparib.
Keywords: chromatin; Drug Resistance, Neoplasm; proteinfosfatasa 2C; poškození DNA; Breast Neoplasms; Chromatin; nádory prsu; DNA repair; genotoxic stress; Cell Proliferation; Phthalazines; protinádorové látky; Homologous Recombination; BRCA1 Protein; Poly(ADP-ribose) Polymerase Inhibitors; Piperazines; Humans; DNA Damage; Antineoplastic Agents; oprava DNA; kontrolní body fáze G2 buněčného cyklu; 53BP1; kontrolní body fáze S buněčného cyklu; Protein Phosphatase 2C; proliferace buněk; homologní rekombinace; Tumor Suppressor p53-Binding Protein 1; DNA Repair; Cell Line, Tumor; nádorové buněčné linie; apoptóza; protein BRCA1; chemotherapy; phosphatase; ftalaziny; HEK293 Cells; PARP inhibitor; G2 Phase Cell Cycle Checkpoints; S Phase Cell Cycle Checkpoints; lidé; piperaziny; HEK293 buňky; Apoptosis; olaparib; PARP inhibitory; chemorezistence